GAYA PENGGUNAAN BAHASA DALAM JUDUL VIDEO DI YOUTUBE: KAJIAN STILISTIKA PRAGMATIK - Hemas Haryas Harja Susetya (UNZAH Genggong, 2020)
Youtube is something that is very popular in Indonesia. One thing that affects the video watched by visitors is the title that labels the video. The purpose of this study is to describe the style of language use in the video title so that we can find out the characteristics of the language of the video title on Youtube. This research is a qualitative descriptive study. The data were collected using the observation method with the basic technique of listening and the advanced technique of taking notes. The data in this study are in the form of video titles on Youtube which contain a distinctive style of using language. This study took data from 20 October 2019 to 20 November 2019. What needs to be emphasized is that the data source is only taken in the column